2023
DOI: 10.1037/xlm0001152
|View full text |Cite
|
Sign up to set email alerts
|

Are logical intuitions only make-believe? Reexamining the logic-liking effect.

Abstract: We like to thank Dries Trippas for providing his materials. We also thank André Aßfalg for technical support with the online data collection.Materials, participant data, and analysis scripts with complete output for all reported experiments can be found in the Open Science Framework archive https://osf.io/9avjc/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(73 citation statements)
references
References 68 publications
10
63
0
Order By: Relevance
“…The current work challenges this view. Our data and modeling of individual responding suggest that, like the logic-liking effect (Hayes et al, 2020; Meyer-Grant et al, 2021), the logic–brightness effect arises from task demands. The current work supports a signal competition account, whereby individuals try to fulfill the demand to make a perceptual discrimination, but when faced with a weak or ambiguous perceptual signal, a subset of participants instead attend to logical structure.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The current work challenges this view. Our data and modeling of individual responding suggest that, like the logic-liking effect (Hayes et al, 2020; Meyer-Grant et al, 2021), the logic–brightness effect arises from task demands. The current work supports a signal competition account, whereby individuals try to fulfill the demand to make a perceptual discrimination, but when faced with a weak or ambiguous perceptual signal, a subset of participants instead attend to logical structure.…”
Section: Discussionmentioning
confidence: 66%
“…These results are analogous to the well-known effects of argument “atmosphere” on judgments of the validity of categorical syllogisms (e.g., Begg & Denny, 1969). Meyer-Grant et al (2021) showed that when these surface features and argument validity are deconfounded, the surface features are more likely to determine liking judgments than actual validity. Hence, an important issue for future work is to compare the relative influences of validity and linguistic surface features on brightness judgments for conditional and disjunctive arguments like those used in the current studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, such an effect continued to appear on pseudo-logical arguments even after participants were trained extensively in deductive logic rules (Ghasemi, Handley, & Stephens, 2022). Meyer-Grant et al (2021) also found similar logical intuition effects on pseudo-logical arguments using a liking judgment task.…”
Section: Matching Heuristicmentioning
confidence: 78%
“…Using conditional inference rules, Ghasemi et al (2022) have suggested that people could elaborate conclusions intuitively, and these inferences impact belief judgments, but these are not logical intuitions. The underlying mechanism of these inferences seemed to be the processing of more superficial structural features that happen to align with logical validity (see also Meyer-Grant et al, 2022, for other recent study that questions the existence of logical intuitions, using conditional and categorical syllogisms tasks).…”
Section: The Dual Process-logical Intuition Model: Are Type 1 Answers...mentioning
confidence: 99%